Far from equilibrium basaltic glass alteration: The influence of Fe redox state and thermal history on element mobilization. (15th March 2020) - Stranghoener, Marius; Dultz, Stefan; Behrens, Harald; Schippers, Axel
Abstract: Elemental release from basaltic glasses at far from equilibrium conditions was investigated as a function of the Fe redox state (Fe(II)/Fetot = 0.35 and 0.80) and thermal history (quenched ↔ annealed). A flow-through column setup was used to ensure disequilibrium of basaltic glass and solution during the entire runtime. Percolation experiments were performed at 25 °C for up to 500 h with intermediate sample collection. Two different pH values were adjusted, and the effect of organic matter was tested by adding oxalic acid. Element concentrations in the percolate were measured by Inductively Coupled Plasma Optical Emission Spectroscopy (ICP-OES). After an initial high release of elements from fresh glass surface, steady state was achieved after 240–430 h for Si at pH 5–7 and after 170–240 h for Al at pH 2. At near neutral conditions (pH 5–7) mobilization of Si is relatively high, while Fe and possibly Al are retained in precipitates. Under more acidic conditions (pH 2), the Si concentration of the solutions was very low compared to the other main constituents of the glass. Large amounts of Si-rich residues are formed after glass dissolution at pH 2. On the other hand, Fe (and Mn) is very mobile under acidic conditions, favored by complex formation with oxalic acid and chlorine. In the initial phase of the pH 2 experiments, the element release from reduced glasses is higher than from oxidized glasses. However, this trend is reversed when approaching steady state. Higher dissolution rates for oxidized glasses are predicted due to the progressive replacement of strong Si-O-Si with weaker Fe(III)-O-Si. At pH 5–7 the concentrations of elements in the percolate are too low to establish a systematic difference between oxidized and reduced glasses. Looking at the total amount of mobilized elements, the thermal history of the glasses has no significant effect in the case of oxalate-free solutions, but a noticeable increase of element release in the case of rapidly quenched glasses was observed when using 1 mM oxalic acid solution. The strong effect of oxalate on dissolution of quenched glasses is probably related to the more open glass network structure in quenched glasses.